The collaborative transplant study registry - Opelz, Gerhard; Döhler, Bernd; Ruhenstroth, Andrea; Cinca, Sofia; Unterrainer, Christian; Stricker, Lilli; Scherer, Sabine; Gombos, Petra; Süsal, Caner; Daniel, Volker; Tran, Thuong Hien (Transplantation reviews, 2013)
The Collaborative Transplant Study (CTS) was initiated in 1982. Over the last 30 years, it has collected information on over half a million kidney, liver, heart, lung, and pancreas transplant procedures. Participation is voluntary and the study has strictly scientific objectives. Analyses of the CTS database serve as an international reference source in the field of solid organ transplantation.